2018
DOI: 10.5114/ain.2018.79992
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of Resources Theory by Stevan E. Hobfoll and prediction of alcohol dependent persons’ abstinence

Abstract: Original article / Artykuł oryginAlny Conservation of resourCes theory by stevan e. hobfoll and prediCtion of alCohol dependent persons' abstinenCe teoria ZaChowania Zasobów stevana e. hobfolla a prZewidywanie utrZymywania abstynenCji prZeZ osoby uzależnione od alkoholu

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
(72 reference statements)
0
9
0
Order By: Relevance
“… 24 Moreover, gratitude may take part in the process of compensation for lost resources, as it allows people to notice and focus on what they have, rather than on what they have lost. Compensation is thought to be “the most effective mechanism for the management of resources”, 48 whenever the lost resources cannot be replaced.…”
Section: Discussionmentioning
confidence: 99%
“… 24 Moreover, gratitude may take part in the process of compensation for lost resources, as it allows people to notice and focus on what they have, rather than on what they have lost. Compensation is thought to be “the most effective mechanism for the management of resources”, 48 whenever the lost resources cannot be replaced.…”
Section: Discussionmentioning
confidence: 99%
“…It seems particularly important to carry out research on people and groups that are short on resources and exposed to their loss, including people at risk of occupational burnout, loss of health, social exclusion, and addictions. Resource-rich people who are in the profit spiral protect and multiply their resources, and in a stressful situation, they are able to reverse the emerging spiral of losses and make a profit (Modrzyński 2018).…”
Section: What Is the Current Situation? What Is Pandemic Stress?mentioning
confidence: 99%
“…Those capable of creating, accumulating, and maintaining resources are less likely to lose them and thus more likely to experience a sense of success and gain, which translates into life satisfaction (Hobfoll, 1998;Skowroński & Talik, 2018;Zhou & Lin, 2016). Research has also confirmed that a gain in personal resources in the group of those at risk of social exclusion can predict increased life satisfaction over time (Modrzyński, 2018).…”
Section: Quality Of Life and Resources Among Those At Risk Of Exclusionmentioning
confidence: 99%
“…The threat of exclusion entails limited access to material, institutional, and social resources, poor health, often destructive environment, and low-quality interpersonal relations (Brandová & Kajanová, 2015;March et al, 2006;Murray, 2007). For example, those with substance addiction often experience rejection from their loved ones and social stigma, which reduces their perceived quality of life (Modrzyński, 2018). Also, the long-term exclusion is accompanied by an expectation of rejection in everyday interactions, experiencing learned helplessness, and emotional difficulties (Wesselmann et al, 2017).…”
Section: Quality Of Life and Resources Among Those At Risk Of Exclusionmentioning
confidence: 99%
See 1 more Smart Citation